Visual pollution phenomena and sensitivity of residences in heritage city centers Case of: Old district of Manama city, Kingdom of Bahrain - ISLAM H. EL-GHONAIMY (Journal of Contemporary Urban Affairs, 2019)
Image of the ancient cities across the Arab region has been changed. The urbanization progress and their subsequent urban changes are of rapid acceleration, due to the population increase in the named cities; affecting the encompassed old districts in many respects. The mentioned changes are forked into two main branches; controlled and uncontrolled. On one side, the controlled category abide by the urban regulations in terms of the visual representation of the old districts. On the other side, the uncontrolled counterpart breaches these regulations and their logical assumptions ending up in many urban problems in general and visual pollution in particular.  The research methodology is staked on both of the data collection and theoretical background about the old district in Manama City, whereas thorough historic background of the city and analytical studies of the selected data and questionnaire is carried out. The Questionnaire design had been started by September 2017 along with a review of prior planning studies and reports relevant to the long-range growth and development of the City. Questions were designed to survey public opinion on specific visual pollution issues and principles. Although there were a few open-ended questions, the majority were closed-ended taking the form of yes/no, multiple-choice, or rating scales. Questions went through several renditions based on intra- and interdepartmental review before being presented. Ending the research by concluding the results and adding recommendation.